Comparative Evaluation of Silver Nanoparticles Gel and Metronidazole Gel with Dental Scaling in Dogs - Patel, Rajeshwary; Parihar, Atul Singh; Gangil, Rakhi; Raghuvanshi, Pavan Diwan Singh; Shrivastava, Nidhi (Indian Journal of Veterinary Sciences and Biotechnology, 2026)
Periodontal disease is one of the most prevalent clinical conditions in dogs, primarily resulting from plaque accumulation and subsequent gingival inflammation. Mechanical debridement through scaling and polishing is considered the standard therapeutic approach; however, adjunct antimicrobial therapy may enhance clinical outcomes. The present study evaluated and compared the efficacy of topical silver nanoparticles gel and metronidazole gel following ultrasonic scaling and polishing in dogs with dental affections. 18 clinical cases were randomly divided into 3 groups (n=6 each), and received scaling and polishing with systemic amoxicillin-clavulanate in group I; topical metronidazole gel in group II, and topical silver nanoparticles gel in group III. Clinical, microbial load, haematological and biochemical parameters were assessed on day 0, 7 and 14. Significant reductions (p
Keywords: Canine; Dental scaling; Metronidazole; Periodontal disease; Silver nanoparticles